Bigger boundaries for sorghum gardens - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The Kakuma Pastoral Development Project in northern Kenya is trying a new method of rainwater harvesting. The method has been tried in about 40 sorghum gardens where it helps to improve water infiltration into the soil, as well as reducing boundary...